Green Accounting and Corporate Social Responsibility (CSR) : Literature Review - Amanda Alvi Nurdiantoro; Indah Oktari Wijayanti; Lulu Amalia Nusron (JURNAL FAIRNESS, 2024)
This review literature aims to explore the relationship between green accounting and Corporate Social Responsibility (CSR) in the context of business sustainability. Green accounting, which focuses on measuring and reporting the environmental impact of a company's activities, plays an important role in supporting CSR initiatives aimed at improving corporate social and environmental responsibility. Through an analysis of various case studies and relevant literature, this review identifies the benefits of implementing green accounting, including improved company reputation, operational efficiency, and stakeholder satisfaction. However, challenges such as lack of understanding, high initial costs, and resistance to change are also faced in the implementation of these practices. The conclusion of this review emphasizes the importance of integrating green accounting in CSR strategies to achieve better sustainability goals. Recommendations for further research and business practices are also presented, with the hope of encouraging companies to be more active in adopting green accounting and CSR as part of their long-term strategies.